Numerical investigations of the flow control effect on a thick wind turbine airfoil using deformable trailing edge flaps. (15th February 2023) - Qian, Yaoru; Zhang, Yuquan; Sun, Yukun; Wang, Tongguang
Abstract: Numerical investigations have been carried out regarding the aerodynamic performance of deformable trailing edge flaps (DTEFs) to reduce the unsteady loads on the FFA-W3-241 airfoil under dynamic stall conditions. Simulations were conducted within the framework of OpenFOAM using Reynolds-averaged Navier-Stokes (RANS) approach with the SST k-ω turbulence model and dynamic mesh technique. The control effects of the DTEF size and deflection angle on the stationary airfoil were evaluated through comparative calculations. Then, comprehensive simulations were conducted to gain a deeper insight into the aerodynamic characteristics of a combined simultaneous airfoil-DTEF oscillating motion. Effects of the flap size, oscillation amplitude, frequency, and phase shifts on the airfoil lift and drag hysteresis loops have been analyzed. When the DTEFs oscillate in the same frequency as the airfoil pitch motion and with the phase shift angle of π, the dynamic load can be effectively alleviated. Under this condition, with the appropriate arrangement of flap size and oscillation amplitude, reduction of the lift fluctuations during dynamic motion can be achieved by a maximum of 42.78%, and the corresponding lift-to-drag ratio can also be regulated within a small variation range at a relatively high level. Highlights: Flow control performance of DTEFs on FFA-W3-241 airfoil was studied using RANS. Effects of the flap size and deflection angle on the static airfoil were evaluated. Aerodynamic responses of simultaneous airfoil-DTEF oscillations were calculated. Effects of the pitching DTEF size, amplitude, frequency and phase were analyzed. The dynamic lift fluctuations can be reduced by 42.78% via harmonic DTEF motions.